Bachtin i wokół Bachtina. Wprowadzenie do kalendarium - Ulicka, Danuta (Przestrzenie Teorii, 2008)
"An introduction to a chronology" considers the probable reasons of the absence in Poland of a monograph of the "life and work of Mikhail Bakhtin" type and also undertakes the complex questions of constructing a chronology (calendar) of his "work and days". It indicates the area of facts and reports which are possible to account for, the inconvenience of introducing them, the necessity of making reductions and cuts. But through this it signals this wider context in which are contained Bakhtin's studies as well as those of the most important members of his circles. Thus in this work is undertaken the (so topical until recently) theoretical problem of the borders of the context which is so indispensable for understanding the text.